Linking foraging behaviour of free-ranging, lactating beef cows with diet quality and weight gain in semi-arid rangeland - David J. Augustine; Monte J. Reed; Sean P. Kearney; Lauren M. Porensky; J. Derek Scasta; David W. Pellatz; Justin D. Derner (Applied Animal Behaviour Science, 2025)

Soil health responses to long-term grazing intensity gradients in two semiarid rangelands - Kalyn Taylor; Justin D. Derner; Daniel Liptzin; Lauren M. Porensky; Jocelyn M. Lavallee; David J. Augustine; David L. Hoover (Agriculture, Ecosystems & Environment, 2025)

Principles for successful livestock grazing management on western US rangelands - Kevin E. Jablonski; Justin D. Derner; Derek W. Bailey; Kirk W. Davies; Paul J. Meiman; Leslie M. Roche; Eric T. Thacker; Lance T. Vermeire; Kim R. Stackhouse-Lawson (Rangelands, 2024)

Adaptive, multi-paddock, rotational grazing management alters foraging behavior and spatial grazing distribution of free-ranging cattle - David J. Augustine; Sean P. Kearney; Edward J. Raynor; Lauren M. Porensky; Justin D. Derner (Agriculture, Ecosystems & Environment, 2023)

Does Grazing Matter for Soil Organic Carbon Sequestration in the Western North American Great Plains? - Justin D. Derner; David J. Augustine; Douglas A. Frank (Ecosystems, 2019)

Contributions of Hydrology to Vesicular Stomatitis Virus Emergence in the Western USA - Emile Elias; D. Scott McVey; Debra Peters; Justin D. Derner; Angela Pelzel-McCluskey; T. Scott Schrader; Luis Rodriguez (Ecosystems, 2019)

Regional grassland productivity responses to precipitation during multiyear above‐ and below‐average rainfall periods - Matthew D. Petrie; Debra P. C. Peters; Jin Yao; John M. Blair; Nathan D. Burruss; Scott L. Collins; Justin D. Derner; Laureano A. Gherardi; John R. Hendrickson; Osvaldo E. Sala; Patrick J. Starks; Jean L. Steiner (Global Change Biology, 2018)
There is considerable uncertainty in the magnitude and direction of changes in precipitation associated with climate change, and ecosystem responses are also uncertain. Multiyear periods of above‐ and below‐average rainfall may foretell consequences of changes in rainfall regime. We compiled long‐term aboveground net primary productivity ( ANPP ) and precipitation ( PPT ) data for eight North American grasslands, and quantified relationships between ANPP and PPT at each site, and in 1–3 year periods of above‐ and below‐average rainfall for mesic, semiarid cool, and semiarid warm grassland types. Our objective was to improve understanding of ANPP dynamics associated with changing climatic conditions by contrasting PPT – ANPP relationships in above‐ and below‐average PPT years to those that occurred during sequences of multiple above‐ and below‐average years. We found differences in PPT – ANPP relationships in above‐ and below‐average years compared to long‐term site averages, and variation in ANPP not explained by PPT totals that likely are attributed to legacy effects. The correlation between ANPP and current‐ and prior‐year conditions changed from year to year throughout multiyear periods, with some legacy effects declining, and new responses emerging. Thus, ANPP in a given year was influenced by sequences of conditions that varied across grassland types and climates. Most importantly, the influence of prior‐year ANPP often increased with the length of multiyear periods, whereas the influence of the amount of current‐year PPT declined. Although the mechanisms by which a directional change in the frequency of above‐ and below‐average years imposes a persistent change in grassland ANPP require further investigation, our results emphasize the importance of legacy effects on productivity for sequences of above‐ vs. below‐average years, and illustrate the utility of long‐term data to examine these patterns.

Native and agricultural forests at risk to a changing climate in the Northern Plains - Linda A. Joyce; Gary Bentrup; Antony S. Cheng; Peter Kolb; Michele Schoeneberger; Justin Derner (Climatic Change, 2018)

Vulnerability of grazing and confined livestock in the Northern Great Plains to projected mid- and late-twenty-first century climate - Justin Derner; David Briske; Matt Reeves; Tami Brown-Brandl; Miranda Meehan; Dana Blumenthal; William Travis; David Augustine; Hailey Wilmer; Derek Scasta; John Hendrickson; Jerry Volesky; et al. (Climatic Change, 2018)

Vulnerability of crops and croplands in the US Northern Plains to predicted climate change - Brian J. Wienhold; Merle F. Vigil; John R. Hendrickson; Justin D. Derner (Climatic Change, 2018)

A narrower gap of grazing intensity. Reply to Fetzel et al., 2017. Seasonality constrains to livestock grazing intensity - Jorge Gonzalo Nicola Irisarri; Sebastián Aguiar; Martin Oesterheld; Justin D. Derner; Rodolfo A. Golluscio (Global Change Biology, 2017)

Quantifying characteristic growth dynamics in a semi-arid grassland ecosystem by predicting short-term NDVI phenology from daily rainfall: a simple four parameter coupled-reservoir model - John F. Hermance; David J. Augustine; Justin D. Derner (International Journal of Remote Sensing, 2015)

Plant community change mediates the response of foliar δ15N to CO2 enrichment in mesic grasslands - H. Wayne Polley; Justin D. Derner; Robert B. Jackson; Richard A. Gill; Andrew C. Procter; Philip A. Fay (Oecologia, 2015)

Western Land Managers will Need all Available Tools for Adapting to Climate Change, Including Grazing: A Critique of Beschta et al. - Tony Svejcar; Chad Boyd; Kirk Davies; Matthew Madsen; Jon Bates; Roger Sheley; Clayton Marlow; David Bohnert; Mike Borman; Ricardo Mata-Gonzàlez; John Buckhouse; Tamzen Stringham; et al. (Environmental Management, 2014)

Linaria dalmatica invades south-facing slopes and less grazed areas in grazing-tolerant mixed-grass prairie - Dana M. Blumenthal; Andrew P. Norton; Samuel E. Cox; Erik M. Hardy; Glen E. Liston; Lisa Kennaway; D. Terrance Booth; Justin D. Derner (Biological Invasions, 2012)

Root responses along a subambient to elevated CO 2 gradient in a C 3 –C 4 grassland - LAUREL J. ANDERSON; JUSTIN D. DERNER; H. WAYNE POLLEY; WENDY S. GORDON; DAVID M. EISSENSTAT; ROBERT B. JACKSON (Global Change Biology, 2010)
Atmospheric CO 2 ( C a ) concentration has increased significantly during the last 20 000 years, and is projected to double this century. Despite the importance of belowground processes in the global carbon cycle, community‐level and single species root responses to rising C a are not well understood. We measured net community root biomass over 3 years using ingrowth cores in a natural C 3 –C 4 grassland exposed to a gradient of C a from preglacial to future levels (230–550 μmol mol −1 ). Root windows and minirhizotron tubes were installed below naturally occurring stands of the C 4 perennial grass Bothriochloa ischaemum and its roots were measured for respiration, carbohydrate concentration, specific root length (SRL), production, and lifespan over 2 years. Community root biomass increased significantly ( P C a over initial conditions, with linear or curvilinear responses depending on sample date. In contrast, B. ischaemum produced significantly more roots at subambient than elevated C a in minirhizotrons. The lifespan of roots with five or more neighboring roots in minirhizotron windows decreased significantly at high C a , suggesting that after dense root growth depletes soil resource patches, plants with carbon surpluses readily shed these roots. Root respiration in B. ischaemum showed a curvilinear response to C a under moist conditions in June 2000, with the lowest rates at C a −1 and peak activity at 450 μmol mol −1 in a quadratic model. B. ischaemum roots at subambient C a had higher SRLs and slightly higher carbohydrate concentrations than those at higher C a , which may be related to drier soils at low C a . Our data emphasize that belowground responses of plant communities to C a can be quite different from those of the individual species, and suggest that complex interactions between and among roots and their immediate soil environment influence the responses of root physiology and lifespan to changing C a .

Grazing and Ecosystem Carbon Storage in the North American Great Plains - Justin D. Derner; Thomas W. Boutton; David D. Briske (Plant and Soil, 2006)

Effects of CO2 enrichment on plant-soil relationships of Lepidium latifolium - Robert R. Blank; Justin D2. Derner (Plant and Soil, 2004)

Above‐ and below‐ground responses of C 3 –C 4 species mixtures to elevated CO 2 and soil water availability - JUSTIN D. DERNER; HYRUM B. JOHNSON; BRUCE A. KIMBALL; PAUL J. PINTER; H. Wayne POLLEY; CHARLES R. TISCHLER; THOMAS W. BOUTTON; ROBERT L. LAMORTE; GERALD W. WALL; NEIL R. ADAM; STEVEN W. LEAVITT; MICHAEL J. OTTMAN; et al. (Global Change Biology, 2003)
We evaluated the influences of CO 2 [Control, ∼ 370 µ mol mol − 1 ; 200 µ mol mol − 1 above ambient applied by free‐air CO 2 enrichment (FACE)] and soil water (Wet, Dry) on above‐ and below‐ground responses of C 3 (cotton, G ossypium hirsutum ) and C 4 (sorghum, Sorghum bicolor ) plants in monocultures and two density mixtures. In monocultures, CO 2 enrichment increased height, leaf area, above‐ground biomass and reproductive output of cotton, but not sorghum, and was independent of soil water treatment. In mixtures, cotton, but not sorghum, above‐ground biomass and height were generally reduced compared to monocultures, across both CO 2 and soil water treatments. Density did not affect individual plant responses of either cotton or sorghum across the other treatments. Total (cotton + sorghum) leaf area and above‐ground biomass in low‐density mixtures were similar between CO 2 treatments, but increased by 17–21% with FACE in high‐density mixtures, due to a 121% enhancement of cotton leaf area and a 276% increase in biomass under the FACE treatment. Total root biomass in the upper 1.2 m of the soil was not influenced by CO 2 or by soil water in monoculture or mixtures; however, under dry conditions we observed significantly more roots at lower soil depths ( > 45 cm). Sorghum roots comprised 81–85% of the total roots in the low‐density mixture and 58–73% in the high‐density mixture. CO 2 ‐enrichment partly offset negative effects of interspecific competition on cotton in both low‐ and high‐density mixtures by increasing above‐ground biomass, with a greater relative increase in the high‐density mixture. As a consequence, CO 2 ‐enrichment increased total above‐ground yield of the mixture at high density. Individual plant responses to CO 2 enrichment in global change models that evaluate mixed plant communities should be adjusted to incorporate feedbacks for interspecific competition. Future field studies in natural ecosystems should address the role that a CO 2 ‐mediated increase in C 3 growth may have on subsequent vegetation change.

Do species evenness and plant density influence the magnitude of selection and complementarity effects in annual plant species mixtures? - H. Wayne Polley; Brian J. Wilsey; Justin D. Derner (Ecology Letters, 2003)
Plant species richness influences primary productivity via mechanisms that (1) favour species with particular traits (selection effect) and (2) promote niche differentiation between species (complementarity). Influences of species evenness, plant density and other properties of plant communities on productivity are poorly defined, but may depend on whether selection or complementarity prevails in species mixtures. We predicted that selection effects are insensitive to species evenness but increase with plant density, and that the converse is true for complementarity. To test predictions, we grew three species of annuals in monocultures and in three‐species mixtures in which evenness of established plants was varied at each of three plant densities in a cultivated field in Texas, USA. Above‐ground biomass was smaller in mixtures than expected from monocultures because of negative ‘complementarity’ and a negative selection effect. Neither selection nor complementarity varied with species evenness, but selection effects increased at the greatest plant density as predicted.

Soil‐ and plant‐water dynamics in a C3/C4 grassland exposed to a subambient to superambient CO 2 gradient - H. WAYNE POLLEY; HYRUM B. JOHNSON; JUSTIN D. DERNER (Global Change Biology, 2002)
Plants may be more sensitive to carbon dioxide (CO 2 ) enrichment at subambient concentrations than at superambient concentrations, but field tests are lacking. We measured soil‐water content and determined xylem pressure potentials and δ 13 C values of leaves of abundant species in a C3/C4 grassland exposed during 1997–1999 to a continuous gradient in atmospheric CO 2 spanning subambient through superambient concentrations (200–560 µmol mol 2−1 ). We predicted that CO 2 enrichment would lessen soil‐water depletion and increase xylem potentials more over subambient concentrations than over superambient concentrations. Because water‐use efficiency of C3 species (net assimilation/leaf conductance; A/g) typically increases as soils dry, we hypothesized that improvements in plant‐water relations at higher CO 2 would lessen positive effects of CO 2 enrichment on A/g. Depletion of soil water to 1.35 m depth was greater at low CO 2 concentrations than at higher CO 2 concentrations during a mid‐season drought in 1998 and during late‐season droughts in 1997 and 1999. During droughts each year, mid‐day xylem potentials of the dominant C4 perennial grass ( Bothriochloa ischaemum (L.) Keng) and the dominant C3 perennial forb ( Solanum dimidiatum Raf.) became less negative as CO 2 increased from subambient to superambient concentrations. Leaf A/g—derived from leaf δ 13 C values—was insensitive to feedbacks from CO 2 effects on soil water and plant water. Among most C3 species sampled—including annual grasses, perennial grasses and perennial forbs—A/g increased linearly with CO 2 across subambient concentrations. Leaf and air δ 13 C values were too unstable at superambient CO 2 concentrations to reliably determine A/g. Significant changes in soil‐ and plant‐water relations over subambient to superambient concentrations and in leaf A/g over subambient concentrations generally were not greater over low CO 2 than over higher CO 2 . The continuous response of these variables to CO 2 suggests that atmospheric change has already improved water relations of grassland species and that periodically water‐limited grasslands will remain sensitive to CO 2 enrichment.